Technology-Enhanced Collaborative Writing (TECW): Malaysian ESL Teachers’ Challenges and Strategies - Abdul Jalil Norshamshizar; Mohamad Maslawati (SHS Web of Conferences, 2024)
Researchers have increasingly turned their attention toward Technology-Enhanced Collaborative Writing (TECW) as a valuable tool for second language acquisition. Despite the rapid adoption of technology in education, there exists a notable research gap concerning the challenges and strategies encountered by Malaysian ESL (English as a Second Language) teachers when incorporating technology into their collaborative writing classrooms. This paper seeks to bridge this gap by shedding light on the specific challenges faced by ESL teachers in Malaysia and the strategies they employ to integrate technology effectively into collaborative writing instruction. The research employs the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) Model to measure these challenges, employing qualitative data collection methods through interviews with four ESL teachers situated in Kuala Lumpur’s Keramat District, all of whom are participants in the Bring-Your-Own-Device (BYOD) pilot program. These findings emphasize the strategies needed for ESL teachers to elevate the quality of their instruction aspects. Ultimately, this research hopes to provide valuable insights to guide teachers in crafting context-specific guidelines for TECW procedures and offers a foundational framework for enhancing ESL instruction in the Malaysian context.